A qualitative assessment of gender roles in child nutrition in Central Malawi - Elizabeth Mkandawire; Clement Bisai; Elizabeth Dyke; Anne Dressel; Hazel Kantayeni; Billy Molosoni; Peninnah M. Kako; Kaboni W. Gondwe; Lucy Mkandawire-Valhmu (BMC, 2022)
Abstract Background Child malnutrition persists globally with men and women playing distinct roles to support children's nutrition. Women frequently carry the bulk of the workload related to food, care, and health, all of which are critical factors in child nutrition. For this reason, development efforts have emphasised women ignoring the potential role of men in supporting children's nutrition. This study sought to understand the different roles that Malawian men and women play in children's nutrition. Methods This qualitative was conducted in rural Central Malawi as part of a baseline study in 2017 for the CARE Southern Africa Nutrition Initiative. Seventy-six participants were interviewed, including 19 men and 57 women, using focus group discussions and in-depth interviews. We sought to understand the gender distribution of men's and women's roles and how these roles influence child nutrition. Results We found that both men and women were involved in productive, reproductive, and community work. However, consistent with the literature, women carried a disproportionate workload in supporting child nutrition compared to men. Women's heavier workloads often prevented them from being able to meet children's food needs. Nevertheless, shifts in gender roles were observed in some of the sampled communities, with men taking up responsibilities that have been typically associated with women. These changes in gender roles, however, did not necessarily increase women's power within the household. Conclusions Traditional gender roles remain prevalent in the sampled communities. Women continue to be primarily responsible for the food, care, and health of the household. Women's heavy workloads prevent them from providing optimal care and nutrition for children. While efforts to advance gender equality by encouraging men to participate in child care and other household responsibilities appear to have had marginal success, the extent to which these efforts have successfully encouraged men to share power remains unclear. Improving gender equality and child nutrition will require efforts to redistribute gendered work and encourage men to move towards shared power with women over household decision-making and control over income.